Out the Summerhill Road : a Novel. - Wood, Jane Roberts (Evelyn Oppenheimer series., 2010)
From Jane Roberts Wood comes a quietly riveting novel revealing the banal faces of evil in a small East Texas town. In 1946 a young couple is brutally murdered in Cold Springs. And, now, thirty-four years later, the rumor is that Jackson Morris, who had been the only person of interest in the murders, has come home. Or has he? When the four women of the Tuesday bridge club hear this rumor, their responses range from a reckless excitement to a shaky uneasiness. There's Isabel, compelling and passionate, who foolishly and inexplicably longs to see Jackson, her first love, again while the seemin.